2004
DOI: 10.1081/erc-200035959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin Supplementation on PCB (Aroclor 1254)‐Induced Changes in Ventral Prostatic Androgen and Estrogen Receptors

Abstract: The objective of this study was to determine the impact of the polychlorinated biphenyl (PCB) Aroclor 1254 and vitamin C and E on ventral prostatic testosterone and estradiol receptor concentration. A group of 30 rats were treated with Aroclor 1254 [2 mg/kg body weight (bwt) /day/ip] for 30 days; 10 rats were treated as Aroclor 1254 control. The remaining 20 rats were subdivided into the following two subgroups of 10 animals each. One group was given vitamin C (500 mg/kg bwt/day/oral) for 10 days, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…26 The PCBs, as xenoestrogens, might affect the production of steroidogenic enzymes and alter the rate of synthesis and metabolism of endogenous estrogens. 41 Several animal studies have reported that PCB treatment affects the steroid receptor levels as well as steroid metabolism 1,42 and circulating androgen concentration. 38 The PCBs, especially the higher chlorinated forms, may selectively induce cytochrome P450s 43 as a possible source of ROS 44 or, alternatively, the oxidation of a broad range of endogenous and exogenous substances (including PCBs).…”
Section: Discussionmentioning
confidence: 99%
“…26 The PCBs, as xenoestrogens, might affect the production of steroidogenic enzymes and alter the rate of synthesis and metabolism of endogenous estrogens. 41 Several animal studies have reported that PCB treatment affects the steroid receptor levels as well as steroid metabolism 1,42 and circulating androgen concentration. 38 The PCBs, especially the higher chlorinated forms, may selectively induce cytochrome P450s 43 as a possible source of ROS 44 or, alternatively, the oxidation of a broad range of endogenous and exogenous substances (including PCBs).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ahmad et al (2003) reported that PCBs treatment significantly decreased testicular size and testosterone levels in plasma and adversely affected spermatogenic activity by disrupting epithelial organization in adult rhesus monkeys (Macaca mulata). Previous studies from our laboratory have shown that Aroclor 1254 decreased sperm motility, sperm count and alters the antioxidant systems of ventral prostate, seminal vesicle and testicular cells (Leydig and Sertoli cells) in adult rats (Anbalagan et al, 2003;Venkataraman et al, 2004aVenkataraman et al, , 2004bSenthilkumar et al, 2004;Sridhar et al, 2004;Vijayababu et al, 2004;Murugesan et al, 2005aMurugesan et al, , 2005b.…”
Section: Introductionmentioning
confidence: 94%
“…PCBs can act as endocrine disrupters and many of such effects are mediated by sex steroid hormone receptors (Cooper and Kavlock, 1997). PCBs can adversely affect male accessory sex glands such as epididymis, prostate, seminal vesicles, which are neglected by testicular hormones (Kaya et al, 2002;Latchoumycandane and Mathur, 2002;Anbalagan et al, 2003;Venkataraman et al, 2004aVenkataraman et al, , 2004bSenthilkumar et al, 2004;Sridhar et al, 2004;Vijayababu et al, 2004;Murugesan et al, 2005aMurugesan et al, , 2005b.…”
Section: Introductionmentioning
confidence: 96%
“…The detrimental impact of PCBs on the neuro-endocrine system development is due to their ability to interact with the mechanism of action of many hormones, including sex steroids. PCB are able to affect steroid production [42,43], to modulate the expression of their receptors [44], as well as to interfere with hormonal steroid receptor binding either as agonists or antagonists, depending on the structure, type of receptor and target organ [45,46]. Many coplanar PCBs have also a dioxin-like activity, interacting with the aryl hydrocarbon receptor (AhR) [47].…”
Section: Environmental Pollutants and Brain Sex Differentiationmentioning
confidence: 99%